History, Culture, and IFC Assistance - Promoting Women's Income Generation in Siwa Oasis - Niethammer, Carmen; Abdella, Heba; Siblini, Kamal M.; Samir Fadl, Nermine (World Bank, Washington, DC, 2012)
Seven hundred miles from Cairo, the Siwa Oasis is located close to the Libyan border in Egypt's Western Desert. Alexander the Great came through here in 331 BC for a consultation with the Oracle of Amun. The remote Oasis was connected to the rest of Egypt only when an asphalt road was built in the 1980s, linking Siwa and Marsa Matruh. Siwa's solitary location has allowed Siwans to maintain their way of life and to preserve their Siwi language. Still today, Siwa is typically reached after a long 8-hour car ride through the desert. Yet it has recently welcomed internationally famous guests, including the Prince of Wales and Queen Paola of Belgium. Among others, the attraction is an International Finance Corporation (IFC)-supported Sustainable Local Development Project implemented by Environmental Quality International (EQI) that includes ecotourism, sustainable agriculture, women's artisanship, and renewable energy.